Assessment of Resource Inputs into Electrical and Electronic Trades in Technical Colleges - Shodeinde, Abidemi O.; Yisa, Mukaila A. (NIU Journal of Humanities, 2020)
This study was a survey research designed to determine the availability, functionality and utilization of human, material and physical resource inputs into the implementation of electrical and electronic trades programme in Ogun state technical colleges. To accomplish these objectives, five research questions were formulated. The entire population of heads of department of electrical and electronic trades, principals and students in six technical colleges in Ogun state, Nigeria were used for the study, because of the relatively small size. A three (3)-section instrument which was face-validated by experts was used for data collection. The data collected from the study was analysed using frequency count, percentages, mean, and standard deviation. The study found that teachers of electrical and electronic trades in Ogun state technical colleges are inadequate, and that student-teacher ratio does not conform to the National Board for Technical Education (NBTE) stipulated standard for technical courses. The study also found that material and physical resources are inadequate. Furthermore, Â¾ of the available resource input into electrical and electronic trades are not functional while only 13% of the available resource inputs are being utilized for the skill acquisition of students. It was therefore recommended that, administrators of technical colleges should strengthen the linkage between technical colleges and industries, to enable access to industrial attachment for both teachers and students. Efforts should also be made by the government through improved funding, to ensure the provision of the minimum required human, material, and physical resources for effective implementation of the electrical and electronic trades programme. Technical college administrators were also advised to devise a system of predictive, preventive, and corrective maintenance in order to ensure that the schoolâ€™s resources are kept in good condition, among others.